ASUHAN KEPERAWATAN PADA NY.K DENGAN POST OPERASI FRAKTUR CALCANEUS DENGAN PEMBERIAN TERAPI MUSIK KLASIK TERHADAP PENURUNAN INTENSITAS NYERI DI RUANG GARDENIA RSUD ARIFIN ACHMAD - Fadila mawadah Fadila (El-Emir Institute, 2025)
The musculoskeletal system is one of the human body systems consisting of bones, joints, muscles and other supporting structures such as tendons, ligaments, functioning as body supports. Calcaneus fracture is a bone injury that occurs in the heel bone caused by a traffic accident. The purpose of this study was to determine the intensity of pain before and after being given classical music therapy to Mrs. K with post-calcaneus fracture surgery, the implementation was carried out for 3 days starting on May 30 - June 1, 2025. Pain was measured using a numeric rating scale (NRS). The results of the study showed that there was a decrease in pain intensity after being given therapy. The pain scale was obtained on the first day of 6 and given therapy until the third day obtained a pain scale of 3. The conclusion is that there is an effect of giving classical music therapy to post-fracture surgery patients. Based on the results of this study, it is recommended that music therapy can be used as a more effective non-pharmacological drug to reduce pain